2020
DOI: 10.1111/ans.16242
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of viral infection from gases and plumes during intra‐abdominal surgery: a systematic scoping review

Abstract: Background: The aim of this study was to identify the current evidence regarding the risk of acquiring viral infections from gases or plumes during intra-abdominal surgery. Peritoneal fluids may contain cellular material and virus particles. Electrocautery smoke and plumes from energy devices may aerosolize harmful substances and viral particles. Insufflation and desufflation during laparoscopic surgery may also aerosolize and distribute biological material. A systematic scoping review was performed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…31,32 In 2020, a review of 24 studies found no evidence of SARS-2-CoV2 in surgical smoke associated with minimally invasive surgery. 33 An Australia and New Zealand group reviewed the evidence to June 2020 34 and found no reports of respiratory viruses or COVID-19 in peritoneal fluid.…”
Section: Is It Dangerous?mentioning
confidence: 99%
“…31,32 In 2020, a review of 24 studies found no evidence of SARS-2-CoV2 in surgical smoke associated with minimally invasive surgery. 33 An Australia and New Zealand group reviewed the evidence to June 2020 34 and found no reports of respiratory viruses or COVID-19 in peritoneal fluid.…”
Section: Is It Dangerous?mentioning
confidence: 99%